Geographies of flight : Phillis Wheatley to Octavia Butler - Decker, William Merrill (Book collections on Project MUSE., 2020)
"Geographies of Flight explores themes of placement and mobility in the work of Olaudah Equiano, Phillis Wheatley, David Walker, Frederick Douglass, Harriet Jacobs, Booker T. Washington, Ida B. Wells Barnett, W. E. B. Du Bois, Richard Wright, Ralph Ellison, Malcolm X, James Baldwin, Toni Morrison, and Octavia Butler"--